Praktik “Nganyareh Kabin” Bagi Pasangan Suami Di Desa Jambekumbu Kecamatan Pasrujambe Kabupaten Lumajang - Achmad Abdillah; Ahmad Fauzi (Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2023)
Legal principles are the main source of laws in the implementation of penal code (criminal law) and other legislation. However, there is a source of living law and a growing development in the life of a tribal law society. Living citizens' laws can also be viewed asa legal source with certain restrictions, as set forth in the 1951 emergency act no. 1 The study aims to analyze how the legal relevance of the legal laws to the enforcing of legal sanctions on the society of tribal law. In the study, the author used the normatif juridical approach with data collection techniques through library studies. Research indicates that the establishment of a legal principle asa source of law in the establishment of criminal sanctions is not the only principle that can be taken asa basis for penalties. However, aside from legality there is also a common principle that lives and flourishes in society, that is, the laws of custom.